DAMPAK EKONOMI DARI MIGRASI: KASUS DI INDONESIA - Sita Dewi; Dwi Listyowati; Bertha Elvy Napitupulu (JURNAL MITRA MANAJEMEN, 2019)
Migration is people mobilization from one area to another area to stay, beyond politica/national limits or administration limits within a country. Migration in Indonesia could take form as internal migration, international migration and also urbanization. Migration has an economical impact to the destination area, but also to the origin.